Clinical Evidence and Mechanisms of High-Protein Diet-Induced Weight Loss - Jaecheol Moon (Journal of Obesity & Metabolic Syndrome, 2020)
Several clinical trials have found that consuming more protein than the recommended dietary allowance not only reduces body weight (BW), but also enhances body composition by decreasing fat mass while preserving fat-free mass (FFM) in both low-calorie and standard-calorie diets. Fairly long-term clinical trials of 6–12 months reported that a high-protein diet (HPD) provides weight-loss effects and can prevent weight regain after weight loss. HPD has not been reported to have adverse effects on health in terms of bone density or renal function in healthy adults. Among gut-derived hormones, glucagon-like peptide-1, cholecystokinin, and peptide tyrosine-tyrosine reduce appetite, while ghrelin enhances appetite. HPD increases these anorexigenic hormone levels while decreasing orexigenic hormone levels, resulting in increased satiety signaling and, eventually, reduced food intake. Additionally, elevated diet-induced thermogenesis (DIT), increased blood amino acid concentration, increased hepatic gluconeogenesis, and increased ketogenesis caused by higher dietary protein contribute to increased satiety. The mechanism by which HPD increases energy expenditure involves two aspects: first, proteins have a markedly higher DIT than carbohydrates and fats. Second, protein intake prevents a decrease in FFM, which helps maintain resting energy expenditure despite weight loss. In conclusion, HPD is an effective and safe tool for weight reduction that can prevent obesity and obesity-related diseases. However, long-term clinical trials spanning more than 12 months should be conducted to further substantiate HPD effects.